NURSING CARE FOR NY.L PATIENTS WITH SCHIZOPHRENIA AUDITING HALLUCINATIONS USING TECHNIQUE INTERVENTION - Stevi Febi Arianti; Fida Dyah Puspasari; Sudiarto (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Background: Hallucinations are where the client cannot differentiate between something that is real and not real. One of the hallucinations that many people experience with schizophrenia is auditory hallucinations. One of the efforts made to overcome hallucinations is by using rebuke of hallucinations. By using the rebuke technique, it is hoped that the level of hallucinations in patients can decrease. Objective: To determine the process of nursing care for schizophrenic patients with sensory perception disorders, auditory hallucinations, using rebuke technique intervention. Method: Using descriptive research with a nursing care approach. Results: The results of the study showed that the signs of hallucinations decreased after the rebuke was carried out. Conclusion: Nursing care was successful and the rebuke technique was able to reduce the frequency of hallucinations.